2010
DOI: 10.1037/a0019055
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioral therapy for 4- to 7-year-old children with anxiety disorders: A randomized clinical trial.

Abstract: Results suggest that developmentally modified parent-child CBT may show promise in 4- to 7-year-old children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(135 citation statements)
references
References 66 publications
(80 reference statements)
4
125
0
3
Order By: Relevance
“…To the best of our knowledge only one study found one aspect of negative affect (behavioral inhibition) in anxious children to have a negative effect on treatment. Cognitive behavioral therapy outcome in 64 children, ages 4-7 was negatively predicted by behavioral inhibition, assessed with observational laboratory protocols (Hirshfeld-Becker et al, 2010). Apart from this study in the very young, negative affect has not been studied in relation to treatment effects in children or adolescents.…”
Section: Child Temperament and Childhood Anxietymentioning
confidence: 95%
“…To the best of our knowledge only one study found one aspect of negative affect (behavioral inhibition) in anxious children to have a negative effect on treatment. Cognitive behavioral therapy outcome in 64 children, ages 4-7 was negatively predicted by behavioral inhibition, assessed with observational laboratory protocols (Hirshfeld-Becker et al, 2010). Apart from this study in the very young, negative affect has not been studied in relation to treatment effects in children or adolescents.…”
Section: Child Temperament and Childhood Anxietymentioning
confidence: 95%
“…In five trials [33][34][35][36][37], a reliable change index [38] was used to identify whether a proportion of participants had deteriorated. Six trials [39][40][41][42][43][44] used the clinical global impression of improvement (CGI-I) [45], which is a clinician-administered scale ranging from 1 (very much improved) to 7 (very much worse). However, only three of these reports included information about the proportion of participants that deteriorated [39,40,44].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Six trials [39][40][41][42][43][44] used the clinical global impression of improvement (CGI-I) [45], which is a clinician-administered scale ranging from 1 (very much improved) to 7 (very much worse). However, only three of these reports included information about the proportion of participants that deteriorated [39,40,44]. Two trials evaluated an intervention for patients with dementia and their caregivers [46,47], and assessed change in caregivers on a scale ranging from 1 (got much worse) to 5 (improved a lot).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Although this four-part model may only provide a broad framework for conceptualizing disability, it likely offers a better overall assessment of how a child with a CHD functions in daily life as compared with alternative measures that focus only on body function/structure or activities. Psychosocial function is highly relevant for children with CHD [42,81]. In fact, Franzblau et al [30] found that 58% of children and 40% of parents reported stress related to their CHD.…”
Section: Discussionmentioning
confidence: 99%